2007
DOI: 10.1007/bf03021894
|View full text |Cite|
|
Sign up to set email alerts
|

Bupivacaïne intrathécale pure vs hyperbare pour l’analgésie du travail obstétrical: efficacité et effets secondaires

Abstract: CAN J ANESTH 54: 1 www.cja-jca.org Januar y, 2007Purpose: Baricity is an important determinant of block characteristics of the spinal component of a combined spinal epidural (CSE) for labour analgesia. This study compares the analgesic efficacy and side effects of intrathecally administered plain and hyperbaric bupivacaine (both with fentanyl) during active labour.Methods: Sixty-two women in active labour (cervical dilatation ≥ 5 cm and pain score > 5) were randomized in a prospective, single-blinded fashion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
2
17
0
2
Order By: Relevance
“…In this issue of the Journal, Rofaeel et al 1 report on a CSE study, examining hyperbaric bupivacaine vs isobaric bupivacaine. The study finds that when added to intrathecal (IT) sufentanil 2.5 µg, isobaric bupivacaine 2.5 mg, the standard dose which many anesthesiologists use, provides better analgesia within the first ten minutes post injection, compared to a 2.5-mg dose of hyperbaric bupivacaine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Journal, Rofaeel et al 1 report on a CSE study, examining hyperbaric bupivacaine vs isobaric bupivacaine. The study finds that when added to intrathecal (IT) sufentanil 2.5 µg, isobaric bupivacaine 2.5 mg, the standard dose which many anesthesiologists use, provides better analgesia within the first ten minutes post injection, compared to a 2.5-mg dose of hyperbaric bupivacaine.…”
mentioning
confidence: 99%
“…Dans ce numéro du Journal, Rofaeel et al 1 font un compte-rendu d'une étude au sujet de la RPC qui compare la bupivacaïne hyperbare à la bupivacaïne isobare. L'étude a trouvé que, lorsqu'elle est ajoutée à du sufentanil intrathécal (IT) 2,5 µg, la bupivacaïne isobare (2,5 mg -la dose standard que de nombreux anesthésiologistes utilisent) offre une meilleure analgésie dans les dix premières minutes post-injection, qu'une dose de 2,5 mg de bupivacaïne hyperbare.…”
unclassified
“…Studies comparing hyperbaric and isobaric bupivacaine reported variable results on spinal anesthesiainduced hypotension (11)(12)(13)(14). In addition to their role in predicting hypotension due to spinal anesthesia, HRV parameters also undergo significant changes following spinal anesthesia (9,10,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of plain versus hyperbaric solutions in intrathecal application of analgesics have shown a similar effect (Srivastava et al, 2004), less effect (Rofaeel et al, 2007), and less side effects (Caute et al, 1988) in the hyperbaric application. However, the effect of trehalose in oral administration of analgesics is not known.…”
Section: Discussionmentioning
confidence: 73%